Aerobic adaptations to resistance training: The role of time under tension - Mang, Z. A.; Ducharme, J. B.; Mermier, C.; Kravitz, L.; de Castro Magalhaes, F.; Amorim, F. (International Journal of Sports Medicine, 2022)
Generally, skeletal muscle adaptations to exercise are perceived through a dichotomous lens where the metabolic stress imposed by aerobic training leads to increased mitochondrial adaptations while the mechanical tension from resistance training leads to myofibrillar adaptations. However, there is emerging evidence for cross over between modalities where aerobic training stimulates traditional adaptations to resistance training (e.g., hypertrophy) and resistance training stimulates traditional adaptations to aerobic training (e.g., mitochondrial biogenesis). The latter is the focus of the current review in which we propose high-volume resistance training (i.e., high time under tension) leads to aerobic adaptations such as angiogenesis, mitochondrial biogenesis, and increased oxidative capacity. As time under tension increases, skeletal muscle energy turnover, metabolic stress, and ischemia also increase, which act as signals to activate the peroxisome proliferator-activated receptor gamma coactivator 1-alpha, which is the master regulator of mitochondrial biogenesis. For practical application, the acute stress and chronic adaptations to three specific forms of high-time under tension are also discussed: Slow-tempo, low-intensity resistance training, and drop-set resistance training. These modalities of high-time under tension lead to hallmark adaptations to resistance training such as muscle endurance, hypertrophy, and strength, but little is known about their effect on traditional aerobic training adaptations.